The Urgency of Improving the Quality of Village Information Systems in Increasing Digital Business in Villages - Kalalo, Rieneke Ryke; Hairul, Hairul; Hamzal, Said; Pratiwi, Dini; Agustina, Ika (Journal Of Human And Education (JAHE), 2024)
Woloan 1 Village is one of the villages in North Tomohon District, Tomohon City, North Sulawesi. Geographically, the location of Woloan 1 Village is very strategic from Tomohon City, North Sulawesi. When discussing with groups of wood craftsmen to make souvenirs in Woloan 1 Village, North Tomohon District, Tomohon City, North Sulawesi, they had a number of problems as well as reasons why regional craft businesses were not developing rapidly. The problem in question is a lack of information and education regarding the marketing of regional craft products in Woloan 1 Village, North Tomohon District. To overcome this problem, an alternative solution that can be implemented is for the author to discuss with village officials who suggest using a digital Village Information System to be able to increase the regional craft business in Woloan 1 Village, North Tomohon District, Tomohon City, North Sulawesi so that it can compete with competitors both online and offline. Therefore, the aim of this community service is to see the potential of using the Digital Village Information System in improving the welfare of the craftsman community in Woloan 1 Village, North Tomohon District, Tomohon City, North Sulawesi. To obtain the data used were observation and literature review. This service activity is an educational effort to improve the digital village information system to improve the welfare of the craftsman community in Woloan 1 Village, North Tomohon District, Tomohon City, North Sulawesi. As a form of the author's thoughts, several efforts and breakthroughs have been offered, namely providing education on how to use the digital village information system so that it can help increase the sustainable business of regional craftsmen in Woloan 1 Village, North Tomohon District, Tomohon City, North Sulawesi.